"CADASIL coma": an underdiagnosed acute encephalopathy. Issue 2 (1st February 2003) - Schon, F; Martin, R J; Prevett, M; Clough, C; Enevoldson, T P; Markus, H S
Abstract : The main clinical features of CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy) are stroke, dementia, and migraine. A reversible acute encephalopathy was the principal presentation in six of 70 patients in a British prevalence study. The episodes lasted seven to 14 days, presenting with fever, acute confusion, coma, and fits; there was full recovery but in two cases identical episodes recurred some years later. All patients had a previous history of migraine with aura and were originally misdiagnosed as viral encephalitis. CADASIL should be considered in acute unexplained encephalopathies. MRI white matter changes, previous migraine with aura, and a family history of stroke and dementia may be useful pointers to the diagnosis.